Catalytic thermochemical conversion of biomass for biofuel production: A comprehensive review. (October 2019) - Ong, Hwai Chyuan; Chen, Wei-Hsin; Farooq, Abid; Gan, Yong Yang; Lee, Keat Teong; Ashokkumar, Veeramuthu
Abstract: The increasing demand for energy and diminishing sources of fossil fuels have called for the discovery of new energy sources. The effective energy conversion process of biomass is able to fulfill energy needs. Among the advanced biomass conversion technologies, thermochemical processes hold considerable potential approaches and needed for optimization. Thus, this study presents a comprehensive review of the research and development on the effects of catalysts on the thermochemical conversion of biomass to determine the progress of catalytic thermochemical conversion processes. The effects of catalysts on torrefaction, pyrolysis, hydrothermal liquefaction, and gasification are highlighted. Aspects related to reaction conditions, reactor types, and products are discussed comprehensively with the reaction mechanisms involved in the catalytic effects. Hydrogenation and hydrodeoxygenation can occur in the presence of zeolite catalysts during fast pyrolysis while producing highly aromatic bio-oil. A heterogeneous catalyst in liquefaction increases the hydrocarbon content and decreases viscosity, acid value, and oxygenated compounds in the bio-oil. Thus, expanding and enhancing knowledge about catalyst utilization in the thermochemical conversion technologies of biomass will play an important role in the generation of renewable and carbon-neutral fuels. Graphical abstract: Image 1 Highlights: AAEMs modify the biomass cellulose structure to enhance thermal reactivity. Zeolites enhance the deoxygenation reactions and aromatic yield. Heterogeneous catalysts enhance hydrocarbon in bio-oil with high recyclability. AAEMs and Ni catalysts promote the H2 content in the gasification process.